Gazetecilik Yıllarında Bülent Ecevit ve Anti-Komünizm (1950-1961) - Ferit Salim SANLI (Gazi Akademik Bakış)
Bülent Ecevit was involved in Turkish intellectual and political life by working as a journalist in the 1950s, and he also entered active politics in the CHP during this time period. In this period, when the Cold War dominated and Turkey showed its side by being included in NATO, Ecevit also spent a lot of time on the issue of communism and gave ample coverage to this issue in his writings. Ecevit, who sees communism as a means for the Soviets' ambitions in Turkey and the world, and thinks that this will create a security threat, argued that the Soviets have ambitions on Turkey and that they use communism as an instrumental in this way. Ecevit also evaluated communism as a problem against the values of Western culture and civilization. Ecevit, who undertook the spokesmanship of the pole described as the "free world" under the leadership of the United States against communism, believed that democracy is as important as military measures in the fight against communism, and that the state should provide social justice and welfare to the citizens in order to eliminate the ground that may cause communism to be favored. Ecevit, who always preserved his CHP identity, used the analogy of the Soviets/iron curtain/communism in his criticisms of the DP, while criticizing the Democrat Party in the struggle against communism.